Morphometric Analysis of Occipital Condyles Using Multi- Detector Computed Tomography - Umar Zakee, Mohammad; Sheikh, Nayeem Ahmad; Bisht, Amit (Journal of Neonatal Surgery, 2025)
Aim The purpose of this work was to assess the morphometric analysis of occipital condyles (OCs) using multi-detector computed tomography (MDCT), as these anatomical structures are essential to the cranial base. Methods The study population comprised 200 OCs from 100 patients, 64 of whom were male and 36 of whom were female, and whose ages ranged from 18 to 70 years. OCs were measured linearly. Result The average OC width, length, height, and effective height were 10.98±1.47 mm, 15.55±1.86 mm, 9.97±2.28 mm & 6.69±1.16. All measurements were found significantly different between right and left sides Also the average intercondylar anterior distance (ICAD) & inter-condylar posterior distance (ICPD) were 16.04±2.90 & 31.78±3.17 respectively. The morphometric measurements varied significantly between age groups. There was a substantial gender difference in all morphometric parameters. Conclusion MDCT can be used to assess OCs' morphometric evaluation in an efficient manner. The OCs' linear measurement data from this study could serve as a reference database for morphometric and surgical research in the future.